2017
DOI: 10.1111/aos.13551
|View full text |Cite
|
Sign up to set email alerts
|

A founder mutation in CERKL is a major cause of retinal dystrophy in Finland

Abstract: Our report indicates that the first diagnostic test for Finnish patients with sporadic or autosomal recessive RD should be a targeted test for founder mutations in the CERKL, EYS, RP1, ABCA4 and GUCY2D genes. These results confirm the utility of NGS-based gene panels as a powerful method for mutation identification in RD, thus enabling improved genetic counselling for these families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 28 publications
5
24
0
Order By: Relevance
“…), and 2.8 kb deletion in CLN3 (), and most recently, c.1155T>A (p.Cys385Ter) in EYS (Avela et al. ), whereas c.148delG in TULP1 , c.2314C>T (p.Gln772Ter) in RPGRIP1 , and c.533G>A (p.Trp178Ter) in TYR were novel findings.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…), and 2.8 kb deletion in CLN3 (), and most recently, c.1155T>A (p.Cys385Ter) in EYS (Avela et al. ), whereas c.148delG in TULP1 , c.2314C>T (p.Gln772Ter) in RPGRIP1 , and c.533G>A (p.Trp178Ter) in TYR were novel findings.…”
Section: Resultsmentioning
confidence: 91%
“…, and Avela et al. ). EYS mutations have been reported in arRP in several European countries, and in Japan and China with variable phenotypes (Littink et al.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The IFT140 gene proposed for patient O was a good fit for the patient's phenotype of retinal dysfunction. However, the variant has a relatively high MAF (1.57% in the Finnish gnomAD cohort) yet is not a major cause of retinal disease in the Finns (Avela et al, ). It was classified therefore as benign.…”
Section: Resultsmentioning
confidence: 99%
“…To date, only one pathogenic mutation in CERKL, c.316C > A (p.Arg106Ser) has been documented in the Pakistani population 7 . Several studies of Yemenite Jewish, Finnish, and Spanish populations have identified mutations in CERKL as a cause of RD 6,[8][9][10] . Importantly, the affected individuals in family PKRP373 and affected individuals described in previously published reports of CERKL-related RD suffer from early and severe involvement of the central retina in addition to peripheral retinal degeneration 6,[8][9][10] .…”
Section: Introductionmentioning
confidence: 99%